Multianalytical Characterization of Lapis Lazuli Pigments of Ajanta Murals for Identification and Its Geological Provenance - Kumar, S. Vinodh; Jaiswal, Vimal Kumar; Mahajan, Anupama S.; Bhatnagar, Manoj Kumar; Rajeswari, L. (Journal of Raman spectroscopy, 2025)
Lapis lazuli is a semiprecious stone that falls under the category of blue‐colored minerals that played a vital role in the cultural historic artwork throughout the world. Finding the provenance of lapis lazuli is a slightly challenging task. The sources of lapis lazuli pigments used at Ajanta Caves and its provenance have been a subject of interest and a research question. Six samples of lapis lazuli pigment of murals of 2nd century bce Ajanta Caves were examined using micro‐Raman spectroscopy, Fourier transform infrared spectrophotometry (FTIR), X‐ray fluorescence spectroscopy, spectrophotometry, X‐ray diffractometry (XRD), and stereomicroscopy to find out the possible provenance raw materials through the mineralogical compositions. This study will be very helpful to tailor future conservation strategies. The results showed that these pigment samples are similar based on their composition, presenting diopside and specific trace element proportions as provenance markers. The results revealed that these raw materials for the lapis lazuli pigments used at Ajanta Caves may have been imported from lapis lazuli mines located at Badakhshan in Afghanistan, as the mines have been actively mined for over 6000 years, making them a significant source of lapis lazuli for ancient civilizations.